2020
DOI: 10.1097/hjh.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Transgender adults, gender-affirming hormone therapy and blood pressure: a systematic review

Abstract: Objectives: Gender-affirming hormone therapy (GHT) is utilized by people who are transgender to align their secondary sex characteristics with their sex identity. Data relating to cardiovascular outcomes in this population are limited. We aimed to review the impact of GHT on the blood pressure (BP) of transgender individuals. Methods: We searched PubMed/MEDLINE, SCOPUS and Cochrane Library databases for articles published relating to the BP of transgender adults commencing GHT. Methodological quality was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…A retrospective study of the effects of estrogen- and testosterone- based GAHT regimens on blood pressure found a slight reduction in systolic blood pressure with the initiation of estrogen-based regimens; while there was a slight elevation (4 mm Hg) in mean systolic blood pressure on long term follow-up of testosterone-based regimens, this difference was at the margin of statistical significance and of limited clinical relevance (Banks et al., 2021 ). A systematic review concluded, given the limited quality of the studies, there is insufficient data to reach conclusions on the effects of gender-affirming hormone therapy on blood pressure (Connelly et al., 2021 ). Spironolactone, often used as an androgen blocker in feminizing GAHT, is a potassium sparing diuretic and may increase potassium when used in conjunction with ACE inhibitors or angiotensin receptor blocker medications, as well as salt substitutes.…”
Section: Chapter 15 Primary Carementioning
confidence: 99%
“…A retrospective study of the effects of estrogen- and testosterone- based GAHT regimens on blood pressure found a slight reduction in systolic blood pressure with the initiation of estrogen-based regimens; while there was a slight elevation (4 mm Hg) in mean systolic blood pressure on long term follow-up of testosterone-based regimens, this difference was at the margin of statistical significance and of limited clinical relevance (Banks et al., 2021 ). A systematic review concluded, given the limited quality of the studies, there is insufficient data to reach conclusions on the effects of gender-affirming hormone therapy on blood pressure (Connelly et al., 2021 ). Spironolactone, often used as an androgen blocker in feminizing GAHT, is a potassium sparing diuretic and may increase potassium when used in conjunction with ACE inhibitors or angiotensin receptor blocker medications, as well as salt substitutes.…”
Section: Chapter 15 Primary Carementioning
confidence: 99%
“…testosterone, estrogens, antiandrogens and gonadotropin-releasing hormone analogs) is used in transgender individuals to favorably modulate their secondary sex characteristics in line with gender identity. There is conflicting evidence from small studies of limited duration on the direction or extent of BP changes in transgender individuals receiving gender-affirming therapies [1027]. It is also undetermined whether transgender hormonal treatments are associated with increased CV risk.…”
Section: Hypertension In Different Demographic Situationsmentioning
confidence: 99%
“…This putative interaction may be of particular importance to the long-term vascular health of transgender individuals receiving gender-affirming hormonal therapy. There is currently insufficient data to advise the impact of sex steroids on blood pressure in this population, however, some studies suggest a higher rate of hypertension [ 75 , 76 ]. It remains unclear to what effect the administration of physiological concentrations of estrogen or testosterone has in natal males and females, respectively, on sex steroid receptor expression or function.…”
Section: Inflammationmentioning
confidence: 99%